From dust they came: government camps and the religion of reform in New Deal California - Ebel, Jonathan H. (North American religions, 2023)
"From Dust They Came tells the story of Dust Bowl refugees' experiences in the camps that New Deal reformers built throughout agricultural California to redeem migratory farm workers from lives of vulnerability and filth, and from pre-modern ways of living and believing"--